City of Knowledge in Twentieth Century Iran: Shiraz, history, and Poetry By Setrag Manoukian (New York: Routledge, 2012. 272 pages.) (American Journal of Islam and Society, 2014)
Setrag Manoukian’s City of Knowledge in Twentieth Century Iran: Shiraz,History, and Poetry combines the application of Michel Foucault’s conceptualizationof the relationship between “knowledge” and “power” with a “historicaland ethnographic investigation” into the sociocultural and political lifeof twentieth-century Shiraz in order to portray a history of Iran and Iraniansthat differs from the usual accounts focusing on Tehran.The book is intended for both Iranian studies scholars and the generalpublic interested in the history of Iran. Avoiding an exclusivist approach thatBook Reviews 107offers either “a national perspective from the capital Tehran” or “a purely localview from a self-contained city,” the book provides, in the author’s words,“the viewpoint of Shiraz as a ‘province’ to highlight how local, national andglobal dimensions are mutually constituted.” It discusses the “question ofknowledge” from the viewpoint of Shiraz because most of the research oncontemporary Iran concentrates on the capital as representative of the wholecountry. In his view, “the after-effect of this concentration on Tehran is an analyticalposture that posits either the state and/or the nation as the startingpoints of the analysis, obliterating the multiplicity of convergences and divergencesfrom which both these constituencies emerge” (p. 3) ...